Struktur Komunitas Ekosistem Mangrove Di Teluk Serewe Pulau Lombok Nusa Tenggara Barat - Irwansyah, Irwansyah; Sugiyarto, Sugiyarto; Mahajoeno, Edwi (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study is to obtain the value of density, frequency, mangrove cover and the mangrove importance index (INP Mangrove) The method used for belt transects. The quadratic transect method measures 10 m x 10 m (tree category), 5 m x 5 m (sapling category) and 2 m x 2 m (seedling category). The results found that the mangrove community in Serewe Bay, Lombok Island, West Nusa Tenggara. Tree strata are dominated by Sonneratia alba species, pole strata are dominated by Sonneratia alba species and the seedling strata are dominated by Pemphis acidula. This shows that the existence of these three types can be found in almost every plot / plot. The Importance Value Index (INP) of mangroves obtained is classified as moderate, this shows that mangroves in Serewe Bay, Lombok Island, West Nusa Tenggara have an important role for the coastal environment.